Economic Challenges and Risks of Cultural Tourism Development in The Context of Globalization - Ilkhamovna, Sattarova Zukhra (American Journal of Economics and Business Management, 2025)
In the era of globalization, cultural tourism has emerged as a dynamic force in international travel, generating significant economic benefits while promoting intercultural dialogue and heritage preservation. However, the rapid expansion of cultural tourism also brings with it a set of complex economic challenges and risks that threaten both the sustainability of local economies and the authenticity of cultural assets. This article examines the economic vulnerabilities associated with cultural tourism development in a globalized context, including over-dependence on international markets, inflationary pressures, seasonal fluctuations, and unequal distribution of income. It also explores the risks of commodification of culture and the displacement of local communities. Drawing on recent case studies, global tourism data, and scholarly literature, the study provides a critical assessment of how global market dynamics influence local cultural tourism economies. The article concludes with strategic policy recommendations aimed at balancing economic growth with cultural integrity and long-term sustainability.​